Plasma Homocysteine Level in Children With Postural Tachycardia Syndrome - Li, Yaqi; He, Bing; Li, Hongxia; Zhang, Qingyou; Tang, Chaoshu; Du, Junbao; Jin, Hongfang (Frontiers in Pediatrics, 2018)
The study was designed to evaluate the changes of plasma homocysteine (Hcy) level in children with postural orthostatic tachycardia syndrome (POTS) and explore its significance. A total of 65 subjects were recruited in our study, of whom 35 children were in the POTS group and 30 healthy children were in the control group. Plasma Hcy levels were determined in all subjects. The relationship between the plasma Hcy level and the symptom score was analysed in the 35 POTS patients. The relationship between the plasma Hcy level and the change in heart rate from the supine to upright position (ΔHR) and between the plasma Hcy level and the rate of increase in heart rate from the supine to upright position (ΔHR/sHR×100%) were analysed in all subjects. The plasma Hcy levels were significantly higher in the children with POTS than those in the control group (9.78 [7.68, 15.31] μmol/L vs 7.79 [7.46, 9.63] μmol/L, P<0.05). The plasma Hcy levels were positively correlated with symptom scores in the POTS patients (n=35, r=0.522, P<0.01). The plasma Hcy levels were also positively correlated with ΔHR (n=65, r=0.332, P<0.01) and ΔHR/sHR×100% (n=65, r=0.341, P<0.01) in all the subjects. In conclusion, the plasma Hcy levels were elevated in the children with POTS positively correlated with the severity of POTS, suggesting that Hcy might be involved in the pathogenesis of POTS.